Diameter index equations for commercial plantations of Pinus pseudostrobus Lindley in Michoacan, Mexico - García-Espinoza, Guadalupe Geraldine; Quiñonez-Barraza, Gerónimo; Aguirre-Calderón, Oscar Alberto; García-Magaña, J. Jesús; Hernández-Ramos, Jonathan (Ecosistemas y Recursos Agropecuarios, 2023)
Commercial forest plantations contribute to increase timber production in forests under management in the state of Michoacan, Mexico; however, the use of equations to efficiently predict the dynamics of diameter growth is not considered, which is essential to plan and evaluate forestry activities. The objective was to fit and compare equations in algebraic difference (ADA) for the elaboration of growth curves and increase in diameter and diameter index for Pinus pseudostrobus in commercial forest plantations in Michoacan, Mexico. The database used comes from stem analysis of 41 trees and for the elaboration of growth curves, the diameter index was considered as the average diameter that plantations reach at reference age of 20 years. The Korf, Levakovic II, Monomolecular and Weibull equations presented high precision according to the fit statistics; but the greatest precision was obtained with the Korf anamorphic equation, which generated curves that adequately described the diameter growth pattern and suggested that the maximum growth point occurs at six years. The diameter index equations are tools that allow adequately describing the growth pattern of the data, in addition, they are useful to estimate the point of maximum growth; this information will be helpful for supporting P. pseudostrobus plantations to lead a higher timber yield.